Inbreeding depression due to recent and ancient inbreeding in Dutch Holstein–Friesian dairy cattle - Doekes, Harmen P.; Veerkamp, Roel F.; Bijma, Piter; de Jong, Gerben; Hiemstra, Sipke J.; Windig, Jack J. (Genetics selection evolution (Paris), 2019)
Inbreeding decreases animal performance (inbreeding depression), but not all inbreeding is expected to be equally harmful. Recent inbreeding is expected to be more harmful than ancient inbreeding, because selection decreases the frequency of deleterious alleles over time. Selection efficiency is increased by inbreeding, a process called purging. Our objective was to investigate effects of recent and ancient inbreeding on yield, fertility and udder health traits in Dutch Holstein-Friesian cows. In total, 38,792 first-parity cows were included. Pedigree inbreeding ([Formula: see text]) was computed and 75 k genotype data were used to compute genomic inbreeding, among others based on regions of homozygosity (ROH) in the genome ([Formula: see text]). Inbreeding depression was observed, e.g. a 1% increase in [Formula: see text] was associated with a 36.3 kg (SE = 2.4) decrease in 305-day milk yield, a 0.48 day (SE = 0.15) increase in calving interval and a 0.86 unit (SE = 0.28) increase in somatic cell score for day 150 through to 400. These effects equalled - 0.45, 0.12 and 0.05% of the trait means, respectively. When [Formula: see text] was split into generation-based components, inbreeding on recent generations was more harmful than inbreeding on more distant generations for yield traits. When [Formula: see text] was split into new and ancestral components, based on whether alleles were identical-by-descent for the first time or not, new inbreeding was more harmful than ancestral inbreeding, especially for yield traits. For example, a 1% increase in new inbreeding was associated with a 2.42 kg (SE = 0.41) decrease in 305-day fat yield, compared to a 0.03 kg (SE = 0.71) increase for ancestral inbreeding. There were no clear differences between effects of long ROH (recent inbreeding) and short ROH (ancient inbreeding). Inbreeding depression was observed for yield, fertility and udder health traits. For yield traits and based on pedigree, inbreeding on recent generations was more harmful than inbreeding on distant generations and there was evidence of purging. Across all traits, long and short ROH contributed to inbreeding depression. In future work, inbreeding depression and purging should be assessed in more detail at the genomic level, using higher density information and genomic time series.